Sustainability-Based Strategic Framework for Digital Transformation in the Oil and Gas Industry - Abdulla Al-Hajri (17151064) (2025)
The oil and gas industry is transforming profoundly, driven by integrating digital technologies to enhance sustainability, operational efficiency, and competitiveness. However, the sector continues to tackle persistent challenges, including fluctuating oil prices, the demand for a stable fuel supply, and increasingly stringent environmental regulations. This paper introduces a sustainability-centered strategic framework for digital transformation within the sector, showcasing the deployment of cutting-edge technologies like data analytics, artificial intelligence (AI), cloud computing, and the Internet of Things (IoT). These advancements address key industry challenges, including operational inefficiencies, safety hazards, and the pressing need to reduce carbon emissions. The research examines the hurdles faced by hydrocarbon-dependent countries, focusing on Qatar’s oil and gas sector, in adopting digital transformation. Through a qualitative case study method involving semi-structured interviews with industry experts, the study identifies critical barriers to digital transformation, organizational resistance to change, a shortage of skilled workers, cybersecurity concerns, and the complexities of integrating new technologies with legacy systems. The findings underscore the pivotal role of digital technologies in improving efficiency, safety, and sustainability, and they highlight the importance of strong leadership and workforce development. The proposed sustainability-based framework provides actionable insights for overcoming these barriers, offering a holistic approach to fostering innovation, enhancing resilience, and aligning digital initiatives with sustainable and business objectives. These results offer valuable guidance for industry leaders and policymakers navigating the complexities of digital transformation in a competitive and sustainable conscious global market. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2025.3548960